2016
DOI: 10.1093/icvts/ivw052
|View full text |Cite
|
Sign up to set email alerts
|

Conventional versus rapid-deployment aortic valve replacement: a single-centre comparison between the Edwards Magna valve and its rapid-deployment successor

Abstract: We conclude that this rapid-deployment valve probably facilitates minimally invasive surgery. Furthermore, a subgroup analysis showed reduced transvalvular gradients in smaller valve sizes compared with the conventionally implanted valve of the same type. The favourable haemodynamic profile and the potentially different spectrum of valve-related adverse events should be addressed in further clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
75
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 13 publications
5
75
0
1
Order By: Relevance
“…We could not detect a time benefit in terms of reduced CPB or aortic clamp time favoring one RDV type over the other. Both RDV have been repeatedly linked to a significant reduction in CPB and aortic clamp time when compared with conventional bioprosthetic AVR [5,6,8,9,19,21], with CPB and aortic cross-clamp times being similar to our report. For example, the Intuity RDV facilitated a 24% reduction in aortic cross-clamp time compared with conventional AVR in the CANDENCE-MIS [8]; and the TRANSFORM investigators reported a clinically meaningful reduction of CPB and aortic clamp time, especially for patients with combined AVR and CABG procedures when compared with the corresponding results of The Society of Thoracic Surgeons Adult Cardiac Surgery Database [5].…”
Section: Commentsupporting
confidence: 88%
“…We could not detect a time benefit in terms of reduced CPB or aortic clamp time favoring one RDV type over the other. Both RDV have been repeatedly linked to a significant reduction in CPB and aortic clamp time when compared with conventional bioprosthetic AVR [5,6,8,9,19,21], with CPB and aortic cross-clamp times being similar to our report. For example, the Intuity RDV facilitated a 24% reduction in aortic cross-clamp time compared with conventional AVR in the CANDENCE-MIS [8]; and the TRANSFORM investigators reported a clinically meaningful reduction of CPB and aortic clamp time, especially for patients with combined AVR and CABG procedures when compared with the corresponding results of The Society of Thoracic Surgeons Adult Cardiac Surgery Database [5].…”
Section: Commentsupporting
confidence: 88%
“…We also found a good stability of hemodynamic variables during follow-up, confirming the 5-year data analysis from the TRITON trial [12] that, although no splitting according to valve size was done, showed no variance of hemodynamic behavior of the Intuity valve over time. Furthermore, Andreas and colleagues [13] found significant Values are mean AE SD or n (%).…”
Section: Commentmentioning
confidence: 98%
“…3,5 However, whether the RD valves are truly beneficial is controversial. 6,7 Therefore, this meta-analysis was conducted to compare the early and follow-up outcomes of AVR using RD valves with conventional bioprosthetic AVR.…”
Section: See Editorial Commentary Page 2413mentioning
confidence: 99%